Hemophagocytic Lymphohistiocytosis Complicating T-Cell Lymphoma in a Patient with HIV Infection - Marc Uemura; Richard Huynh; Allen Kuo; Fernando Antelo; Robert Deiss; James Yeh (Case Reports in Hematology)
Hemophagocytic lymphohistiocytosis (HLH), while uncommon, may be a devastating complication of lymphoma and/or human immunodeficiency virus (HIV) infection. While several of the diagnostic criteria for HLH are relatively nonspecific, particularly in the setting of a systemic inflammatory response, more diagnostic specificity may be achieved with marked elevations in serum ferritin (e.g., >100,000 ng/mL). Increased suspicion of HLH, particularly in the setting of persistent, unexplained fevers, pancytopenia, and transaminitis, should prompt consideration of HLH. Earlier diagnosis and initiation of therapy have the potential to alter the natural history and poor prognosis of this disorder. We present a patient with HIV infection who developed relapsed T-cell lymphoma complicated by hemophagocytic lymphohistiocytosis.